Dach1 Extends Artery Networks and Protects Against Cardiac Injury. Issue 7 (12th August 2021) - Raftrey, Brian; Williams, Ian; Rios Coronado, Pamela E.; Fan, Xiaochen; Chang, Andrew H.; Zhao, Mingming; Roth, Robert; Trimm, Emily; Racelis, Raquel; D'Amato, Gaetano; Phansalkar, Ragini; Nguyen, Alana; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Coronary artery disease is the leading cause of death worldwide, but there are currently no methods to stimulate artery growth or regeneration in diseased hearts. Studying how arteries are built during development could illuminate strategies for re-building these vessels during ischemic heart disease. We previously found that Dach1 deletion in mouse embryos resulted in small coronary arteries. However, it was not known whether Dach1 gain-of-function would be sufficient to increase arterial vessels and whether this could benefit injury responses. Objective: We investigated how Dach1 overexpression in endothelial cells affected transcription and artery differentiation, and how it influenced recovery from myocardial infarction. Methods and Results: Dach1 was genetically overexpressed in coronary endothelial cells in either developing or adult hearts using ApjCreER. This increased the length and number of arterial end branches expanded arteries during development, in both the heart and retina, by inducing capillary endothelial cells to differentiate and contribute to growing arteries. Single-cell RNA sequencing of endothelial cells undergoing Dach1 -induced arterial specification indicated that it potentiated normal artery differentiation, rather than functioning as a master regulator of artery cell fate. Single-cell RNA sequencing also showed that normal arterial differentiation is accompanied by repression of lipid metabolism genes, which were also repressed by Dach1. In adults, Dach1 overexpression did not cause a statistically significant change artery structure before injury, but increased the number of perfused arteries in the injury zone post-myocardial infarction. Conclusions: Our data demonstrate that increasing Dach1 is a novel method for driving artery specification and extending arterial branches, which could be explored as a means of mitigating the effects of coronary artery disease.